Gestão municipal e desenvolvimento rural no Ceará - Insaurralde, Paula Andréia Bezerra (2024)
Rural development is not just limited to agriculture, but also encompasses social, economic, environmental and infrastructure issues. To be achieved, there must be a network of connected agents where each one performs their specific functions. Among these agents, local public authorities have received little attention from researchers interested in developing rural development models. This is a gap given that studies prove the importance of municipal government, via the implementation of management instruments, for the effectiveness of sectoral policies in education, health and public security. It should also be noted that the impacts on rural development generated by good municipal management can spread to neighboring municipalities, promoting gains for the region's population as a whole. In this scenario, the research hypothesis is that municipal agricultural management is a determining factor for the rural development of the municipality, with consequences for neighboring municipalities. Thus, the general objective is to analyze the importance of municipal agricultural management for rural development in Ceará. To this end, secondary data on a municipal scale were used. Systems of indicators distributed in dimensions of municipal management of agriculture and rural development were analyzed and from them metrics of the two concepts were obtained, represented by the indices: Minicipal Agricultural Management Index (IGAP) and Rural Development Index. The relationship between IGAP and IDR was analyzed using linear correlation coefficient and bivariate spatial analysis statistics, specifically Global Moran Index and bivariate LISA. The results showed low levels of implementation of agricultural support instruments by local authorities. It was also observed that the majority of municipalities are in classes with a low level of rural development. The spatial analysis highlighted the heterogeneity between municipalities. A very small group finds itself in a favorable situation of higher levels of both public agricultural management and rural development. In most municipalities, the hypothesis that rural development is associated with agricultural management, with spillovers to neighboring municipalities, was refuted. In this way, it was possible to conclude that, in general, the actions of local authorities are not managing to significantly impact local indicators of rural development and are not even managing to intervene in the conditions of their neighbors. The exceptions identified in the hotpot clusters (15 municipalities distributed in the intermediate regions of Fortaleza, Quixadá and Juazeiro do Norte) can serve as a model for implementing strategies to reverse the deficient situation observed in the rest of the State.